Rate effects on transformation kinetics in a metastable austenitic stainless steel. (2017) - Alturk, Rakan; Luecke, William E.; Mates, Steven; Araujo, A.; Raghavan, K.S.; Abu-Farha, Fadi
Abstract: In this study, the effects of strain rate on the mechanical properties and the strain-induced austenite-to-martensite transformation in type 201 austenitic stainless steel (SS201) were investigated. This grade was selected as a low-cost stainless steel with good lightweighting potential for automotive applications. The material was tested in tension at a quasi-static rate (5x10 -2 s -1 ), two low-intermediate rates (10 0 s -1 and 10 1 s -1 ), and a high rate (5x10 2 s -1 ). 3D digital image correlation was used to enable accurate strain measurements during mechanical testing. Magnetic induction and X-ray diffraction were used ex-situ of deformation to measure the volume fraction of martensite formed at each strain rate, for different plastic strain levels. The effects of strain rate on deformation-induced martensite formation and on the stress/strain behavior was determined in this study, and was compared to results reported in the literature for 300 series austenitic stainless steels. The results show a favourable response for the SS201, which exhibits a substantial increase in strength and energy absorption at high rates without compromising tensile ductility.